A hepatopancreatic microsporidian in pond-reared tiger shrimp, penaeus monodon, from Malaysia - Anderson, I. G.; Shariff, Mohamed; Nash, G. (Elsevier, 1989)
Microsporidian parasites are known from a number of different wild and cultured penaeid species in North America (J. A. Couch, Fish. Bull. 76, 1-44, 1978; V. Sprague, 1977 in “Comparative Pathobiology," L. A. Bulla, Jr., and T. C. Cheng, Eds., Vol. 2, pp. 335-386, Plenum Press, New York). More recently, M. L. C. Baticados and G. L. Enriques (Nat. Appl. Sci. Bull. 34, 255-271, 1982) described a microsporidian infection of Penaeus rnerguiensis from the Philippines affecting the ovary of adults. This communication reports a microsporidian infection of P. monodon hepatopancreatocytes associated with low production in brackishwater pond culture.